Insect masquerades. (New York, Viking Press, 1968)
Surveys the many techniques and devices used by insects to trap prey or escape their enemies through camouflage or trickery.
Bibliography: p. [91]
Keywords: Insects -- Juvenile literature; Mimicry (Biology) -- Juvenile literature; Camouflage (Biology); Insects -- Habits and behavior